Jam Kosong & Upaya Guru Mengatasinya di Sekolah Dasar - Alifah Asma Amalia; Muhammad Abduh (Jurnal Elementaria Edukasia, 2023)
There are three main components in education, namely teachers, students, and an effective curriculum that must collaborate in the learning process in order to create effective learning and achieve goals. The following three components have the same goal with different roles so that they cannot be separated. If one of them is missing then learning can run ineffectively. This research aims to explore more deeply how teachers manage supervision during free time. The research method uses descriptive qualitative analytical techniques and research subjects are taken from the principal, teachers and students of SD N 2 Canden. Data collection techniques are by means of observation, interviews and documentation. Data analysis technique with several stages, namely data collection, data reduction, data presentation and drawing research conclusions. The results and discussion show that several teachers left the classroom due to illness, training, community activities and teacher mobilization. during free time, it is still supervised by a teacher who is not there at that time or the teacher who is closest to the empty class and appoints several students to coordinate the class. The conclusion of this research is that the teacher's efforts to overcome this are by giving assignments by adjusting the material being studied and providing additional hours if there is material that is left behind